Fgf2 improves functional recovery—decreasing gliosis and increasing radial glia and neural progenitor cells after spinal cord injury. Issue 2 (13th January 2014) - Goldshmit, Yona; Frisca, Frisca; Pinto, Alexander R.; Pébay, Alice; Tang, Jean‐Kitty K. Y.; Siegel, Ashley L.; Kaslin, Jan; Currie, Peter D.
Abstract Objectives A major impediment for recovery after mammalian spinal cord injury (SCI) is the glial scar formed by proliferating reactive astrocytes. Finding factors that may reduce glial scarring, increase neuronal survival, and promote neurite outgrowth are of major importance for improving the outcome after SCI. Exogenous fibroblast growth factor (Fgf) has been shown to decrease injury volume and improve functional outcome; however, the mechanisms by which this is mediated are still largely unknown. Methods In this study, Fgf2 was administered for 2 weeks in mice subcutaneously, starting 30 min after spinal cord hemisection. Results Fgf2 treatment decreased the expression of TNF‐a at the lesion site, decreased monocyte/macrophage infiltration, and decreased gliosis. Fgf2 induced astrocytes to adopt a polarized morphology and increased expression of radial markers such as Pax6 and nestin. In addition, the levels of chondroitin sulfate proteoglycans (CSPGs), expressed by glia, were markedly decreased. Furthermore, Fgf2 treatment promotes the formation of parallel glial processes, "bridges, " at the lesion site that enable regenerating axons through the injury site. Additionally, Fgf2 treatment increased Sox2‐expressing cells in the gray matter and neurogenesis around and at the lesion site. Importantly, these effects were correlated with enhanced functional recovery of the left paretic hind limb. Conclusions Thus, early pharmacological intervention with Fgf2 following SCI is neuroprotective and creates a proregenerative environment by the modulation of the glia response.